A mediator-based approach for decentralised production planning, scheduling and monitoring - Tönshoff, H.-K. (2010)
The improvement of business processes along the supply chain has become a focus in industry and research during the past decade. Based on advanced technologies for communication and data structuring this paper describes a software system called the Mediator that provides support for integrating decision-making of several separate actors in decentralized business organizations. The Mediator is designed to offer an adequate level of decision-making integration, taking into account the effort needed for the integration of heterogeneous computer systems by use of the Extended Mark-up Language (XML). The approach is demonstrated for industrial pilot cases in multi-site and supply-chain production.